Abnormal static and dynamic functional connectivity of striatal subregions in patients with obsessive-compulsive disorder - Shi, Wenqing; Tian, Ya; Yang, Huiting; Guo, Huirong; Wen, Baohong; Liu, Zijun; Zhang, Yong; Han, Shaoqiang; Cheng, Jingliang (Frontiers in Psychiatry, 2025)
BackgroundAs a crucial node of the cortico-striato-thalamo-cortical (CSTC) loop, the striatum has long been considered to be involved in the pathophysiology of obsessive-compulsive disorder (OCD). Numerous neuroimaging studies have reported functional abnormalities of the striatum in OCD. However, altered dynamic functional connectivity (DFC) patterns of striatal subregions were rarely reported in patients with OCD.MethodsWe collected resting-state functional MRI data from 97 first episode and drug-naïve OCD patients and 106 HCs matched for gender and age. Seed-based whole-brain resting-state functional connectivity (RSFC) and DFC analysis were performed for 12 striatal subregions. Between-group differences of the mean RSFC and DFC were determined using a two-sample t-test. In addition, we performed a Spearman’s correlation analysis to examine the relationship between altered RSFC and DFC and the clinical characteristics of OCD.ResultsPatients with OCD exhibited increased RSFC between the superior ventral striatum (VSs) and the calcarine (CAL), lingual gyrus (LING), cuneus (CUN), supplementary motor area (SMA), precuneus (PCUN), paracentral lobule (PCL) and superior parietal gyrus (SPG). Increased RSFC between the left dorsal caudal putamen (DCP) and LING and inferior occipital gyrus (IOG) and increased RSFC between left ventral rostral putamen (VRP) and fusiform gyrus (FFG) were also found. in OCD group. The left dorsal caudate (DC) showed increased RSFC with CAL. In addition, OCD patients shows increased RSFC between multiple striatal seeds and cerebellum. The left VSs showed decreased DFC in the OCD patients with the PCUN, SPG and superior occipital gyrus (SOG). The right DC showed decreased DFC with the medial frontal gyrus orbital part (ORBmed), superior frontal gyrus orbital part (ORBsup) and gyrus rectus (REC). OCD severity was associated with DFC values between the right DC and ORBmed (r = 0.209, p = 0.044).ConclusionOur study reveals disrupted RSFC and DFC between the striatal subregions and widespread brain regions in OCD patients. The findings highlight the role of the striatum in the neuropathology of OCD at a refined anatomical level and support the CSTC model in OCD.